Talent development in gifted education theory, research, and practice - VanTassel-Baska, Joyce (Routledge, 2022)
This volume brings together experts in gifted education to explore critical perspectives in talent development across the lifespan, guiding readers toward a deeper understanding of advanced learners and their education. Chapters in the first section delve into the foundational theory, research, and models of practice underpinning gifted education and talent development, while the second section examines the practical applications of talent development in assessment, programming, and ongoing research. The book concludes with an exploration of talent throughout the lifespan, featuring detailed case vignettes to illustrate development across diverse fields of practice. Ideal for researchers as well as students of gifted education and creativity studies, this comprehensive handbook challenges readers to interrogate what they think they know about giftedness and talent development.